A genome-wide association scan identifies the hepatic cholesterol transporter ABCG8 as a susceptibility factor for human gallstone disease - Buch, Stephan; Schafmayer, Clemens; Völzke, Henry; Becker, Christian; Franke, Andre; von Eller-Eberstein, Huberta; Kluck, Christian; Bässmann, Ingelore; Brosch, Mario; Lammert, Frank; Miquel, Juan Francisco; Nervi, Flavio; et al. (Nature genetics, 2007)
With an overall prevalence of 10–20%, gallstone disease (cholelithiasis) represents one of the most frequent and economically relevant health problems of industrialized countries 1 , 2 . We performed an association scan of >500,000 SNPs in 280 individuals with gallstones and 360 controls. A follow-up study of the 235 most significant SNPs in 1,105 affected individuals and 873 controls replicated the disease association of SNP A-1791411 in ABCG8 (allelic P value P CCA = 4.1 × 10 −9 ), which was subsequently attributed to coding variant rs11887534 (D19H). Additional replication was achieved in 728 German ( P = 2.8 × 10 −7 ) and 167 Chilean subjects ( P = 0.02). The overall odds ratio for D19H carriership was 2.2 (95% confidence interval: 1.8–2.6, P = 1.4 × 10 −14 ) in the full German sample. Association was stronger in subjects with cholesterol gallstones (odds ratio = 3.3), suggesting that His19 might be associated with a more efficient transport of cholesterol into the bile.